Rational Design and in-situ Synthesis of Ultra-Thin β-Ni(OH)2 Nanoplates for High Performance All-Solid-State Flexible Supercapacitors - Wang, Shensong; Tan, Changqin; Fei, Linfeng; Huang, Haitao; Zhang, Shujun; Huang, Hao; Zhang, Xinyi; Huang, Qiu-an; Hu, Yongming; Gu, Haoshuang (Frontiers in Chemistry, 2020)
The all-solid-state flexible supercapacitor (AFSC), one of the most flourishing energy storage devices for portable and wearable electronics, attracts substantial attentions due to their high flexibility, compact size, improved safety and environmental friendliness. Nevertheless, the current AFSCs usually show low energy density, which extremely hinders their practical applications. Herein, ultra-thin β-Ni(OH)2 nanoplates with thickness of 2.4 nm are in-situ grown uniformly on Ni foam by one step hydrothermal treatment. Thanks to the ultra-thin nanostructure, β-Ni(OH)2 nanoplates shows a specific capacitance of 1452 F g-1 at the scan rate of 3 mV s-1. In addition, the assembled asymmetric AFSC (Ni(OH)2//Activated carbon) shows a specific capacitance of 198 F g-1. It is worth noting that the energy density of the AFSC can reach 62 Wh kg-1 while keeping a high power density of 1.5 kW kg-1. Furthermore, the fabricated AFSCs exhibit satisfied fatigue behavior and excellent flexibility, and about 82% and 86% of the capacities were retained after 5000 cycles and folding over 1500 times, respectively. Two AFSC in series connection can drive the electronic watch and to run stably for 10 minutes under the bending conditions, showing a great potential for powering portable and wearable electronic devices.